Technical Failures in Helicopters: Non-Powerplant-Related Accidents - Alex de Voogt; Keyashia Nero (Safety, 2023)
Technical failures in helicopters are a main concern for helicopter safety. The prominence of mechanical failures differs for specific helicopter operations. This analysis used 151 General Aviation accident reports from the National Transportation Safety Board online database from an 11-year time period. The information in each report was collated, including the list of findings for each accident. Possible relations between causes and specific flight operations were analyzed by looking at significant differences between expected and actual values within the dataset of categorical data. It is found that the proportion of fatal accidents in this category of accidents is low (16.6%) compared with the percentage of fatal helicopter accidents in general, as well as those of specific helicopter operations. Instructional flights appear significantly more likely to be associated with maintenance-related causes. Causes related to fatigue of aircraft parts are more often associated with ferry and positional flights, as well as helicopters with turbo-shaft engines. Future research is recommended for these specific associations to further mitigate the number of accidents with non-powerplant failures.